MRT Operational Cost Optimization with Lingo Programming and the Vogel Approximation Method - Isna Nugraha; Farida Pulansari; Tivani Nava Arier; Achmad Gufron (Future Science, 2023)
When the MRT was first operated, operations ran smoothly and it is hoped that this condition will continue to be optimal in the long term and have efficient operational costs. As a corporation that offers transportation services, PT MRT XYZ distributes passengers. Fixed expenses, variable costs, and travel costs all have an impact on efficient operational costs. Minimizing operational costs to support other costs, like maintenance costs, is vital for MRT XYZ operations to run as efficiently as possible. The study's goal is to determine the MRT system's operating expenses. The optimal operational costs, which were determined by using the travel matrix computation, were IDR 1,267,110,000,000 based on the analysis and discussion's findings. The factors utilized according to Tyonardo, the MRT station area's function and the costs that affect operations are used to determine the variable number of passengers using financial modeling. Optimizing language costs is anticipated to be the primary determinant in deciding how much profit PT MRT will make.